Clinical Comparison of ICD Detection Algorithms that Include Rapid-VT Zones - HIRSH, DAVID S.; CHINITZ, LARRY A.; BERNSTEIN, NEIL E.; HOLMES, DOUGLAS S.; RAO, SATYA; AIZER, ANTHONY (Pacing and clinical electrophysiology, 2012)
Introduction: The safe use of antitachycardia pacing (ATP) to terminate rapid ventricular tachycardias (VTs) (cycle length 240–320 ms) is predicated on the ability of implantable cardioverter defibrillators (ICDs) to distinguish rapid VT from ventricular fibrillation (VF). We set out to compare the time to device charging following the induction of VF of various ICD multizone detection algorithms for rapid VT/VF discrimination. Methods and Results: Data on the time to device charging following the induction of VF at the time to device implantation were collected on 62 consecutive patients in a nonrandomized prospective cohort fashion. Multizone programming for the Boston Scientific, Medtronic, and St. Jude Medical devices was based on prior clinically validated data. Sixty‐two subjects were studied (Boston Scientific = 16, Medtronic = 27, St. Jude Medical = 19) and 124 tests for VF detection were performed (Boston Scientific = 32, Medtronic = 54, St. Jude Medical = 38). Mean time to charging was significantly prolonged in the Boston Scientific group as was the percentage of tests where charge initiation occurred >5 seconds from VF‐induction: 4.24, 3.99, and 3.00 seconds and 19%, 4%, and 0% for the Boston Scientific, Medtronic, and St. Jude Medical groups, respectively, P < 0.05. ATP was the first therapy administered in 9.4% of tests in the Boston Scientific group. Conclusion: The Boston Scientific multizone VT/VF discrimination algorithm results in a prolonged time to VF detection, and consequently, prolonged time to appropriate initiation of device charging. Further studies are needed to determine whether prolonged detection times lead to clinically significant events. (PACE 2012; 35:1222–1231)